Safety and Efficacy of Animal Derived Surfactants in Treating Preterm Infants with Respiratory Distress Syndrome: A Retrospective Cohort Study - Dong, Xiaoao; Alim, Abdul Haium Abdul; Saffari, Seyed Ehsan; Chua, Mei Chien; Rajadurai, Victor Samuel; Chandran, Suresh (Archives of Clinical and Medical Case Reports, 2021)
Background: Animal-derived surfactants contain different chemical compositions with various responses, efficacy and safety profiles in treating preterm infants with respiratory distress syndrome. The study aimed to compare the safety and efficacy between poractant alfa (Curosurf®) and beractant (Survanta®) in preterm infants requiring endotracheal surfactant therapy. Methods: This is a single-center, retrospective observational cohort study involving preterm infants who required endotracheal surfactant therapy at our hospital from January 2015 to January 2016. Incidence of pneumothorax, chronic lung disease (CLD), mortality, and the composite outcome of CLD and death were compared between the infants who received poractant alfa and beractant. Results: Overall, 179 preterm infants received endotracheal surfactants. Of these, 70 (31%) and 109 (69%) received poractant alfa and beractant, respectively. The incidence of pneumothorax in infants treated with poractant alfa was significantly lower than those treated with beractant (0.00% vs. 6.42%, P = 0.031). Compared with beractant, poractant alfa significantly reduced the incidence of pneumothorax in very low birth weight (VLBW) infants (0.00% vs. 8.00%, P = 0.035), but not in non-VLBW infants (poractant alfa 0.00% vs. beractant 3.03%, P = 1.00). The rates of CLD, mortality, and composite outcomes of CLD and death were not different between the two groups. Conclusions: Poractant alfa significantly reduced the rates of pneumothorax in preterm infants with respiratory distress syndrome. This reduction was more significant in VLBW than non-VLBW infants. However, mortality and morbidity were not different between these two groups.